Can nirmatrelvir/ritonavir treatment shorten the duration of COVID-19 isolation? - Kim, Haein; Yang, Jeong-Sun; Ko, Jae-Hoon; Lee, Myungsun; Lee, Joo-Yeon; Park, Sehee; Kim, Jun-Won; Shin, Younmin; Lee, Jung-Min; Na, Yoo Jin; Park, Byoung Kwon; Kim, Hyungjin; et al. (Frontiers in Medicine, 2022)
Background: The impact of nirmatrelvir/ritonavir treatment on shedding of viable virus in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is unclear. Methods: A prospective cohort study evaluating mildly ill COVID-19 patients was conducted. Virologic responses were compared between nirmatrelvir/ritonavir-treatment and supportive care groups. Risk factors and relevant clinical factors for shedding of viable virus were investigated. Results: A total of 80 COVID-19 patients were enrolled and 222 sputum specimens were collected. Ten patients were dropped during follow up, and 33 patients in the nirmatrelvir/ritonavir and 37 in the supportive care groups were compared. The median age was 67 years, and 67% were male. Clinical characteristics were similar between groups. Viral loads decreased significantly faster in the nirmatrelvir/ritonavir group compared with the supportive care group (P < 0.001), and the slope was significantly steeper (−2.99 ± 1.54 vs. −1.44 ± 1.52; P < 0.001). Duration of viable virus shedding was not statistically different between groups. In the multivariable analyses evaluating all collected specimens, male gender (OR 2.51, 95% CI 1.25–5.03, P = 0.010), symptom score (OR 1.41, 95% CI 1.07–1.87, P = 0.015), days from symptom onset (OR 0.72, 95% CI 0.59–0.88, P = 0.002), complete vaccination (OR 0.09, 95% CI 0.01–0.87, P = 0.038), and BA.2 subtype (OR 0.49, 95% CI 0.26–0.91, P = 0.025) were independently associated with viable viral shedding, while nirmatrelvir/ritonavir treatment was not. Conclusions: Nirmatrelvir/ritonavir treatment effectively reduced viral loads of SARS-CoV-2 Omicron variants, but did not decrease the duration of viable virus shedding.